2022
DOI: 10.1101/2022.06.20.496617
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differences in neurotoxic outcomes of organophosphorus pesticides revealed via multi-dimensional screening in adult and regenerating planarians

Abstract: Organophosphorus pesticides (OPs) are a chemically diverse class of commonly used insecticides. Epidemiological studies suggest that low dose chronic prenatal and infant exposures can lead to life-long neurological damage and behavioral disorders. While inhibition of acetylcholinesterase (AChE) is the shared mechanism of acute OP neurotoxicity, OP-induced developmental neurotoxicity (DNT) can occur independently and/or in the absence of significant AChE inhibition, implying that OPs affect alternative targets.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 125 publications
2
5
0
Order By: Relevance
“…Comparing outcomes for the two developmental stages, we discovered that many of the tested compounds caused differential effects in adult versus regenerating planarians. Lethality was generally induced at the same or lower concentrations in adult planarians than in regenerating planarians, similar to previously observed trends (Zhang et al 2019a; Ireland et al 2022). Only mianserin caused lethality at lower concentrations in regenerating planarians than in adults.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Comparing outcomes for the two developmental stages, we discovered that many of the tested compounds caused differential effects in adult versus regenerating planarians. Lethality was generally induced at the same or lower concentrations in adult planarians than in regenerating planarians, similar to previously observed trends (Zhang et al 2019a; Ireland et al 2022). Only mianserin caused lethality at lower concentrations in regenerating planarians than in adults.…”
Section: Discussionsupporting
confidence: 89%
“…The interpretation of these differences is difficult because the molecular regulation of noxious heat sensation and the planarians’ behavioral responses are poorly understood. Cholinergic signaling seems to be involved in regulating planarian behavior in response to noxious heat because chemical and molecular inhibition of acetylcholinesterase can cause defects in these endpoints (Hagstrom et al 2018b; Zhang et al 2019b; Ireland et al 2022). However, the identity of the heat sensitive receptors in D. japonica remains to be determined (Sabry et al 2019) as well as how the initial noxious heat sensation is processed in the nervous system to cause the stereotypical muscle-driven periodic body length scrunching oscillations (Cochet-Escartin et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that D. japonica has two ChE genes with intermediate characteristics between AChE and butyrylcholinesterase (Hagstrom et al 2017(Hagstrom et al , 2018 that are sensitive to OP inhibition and can be reactivated by oximes. Furthermore, we have shown that different OPs have varying potency and cause different behavioral phenotypes in developing and adult planarians (Hagstrom et al 2015;Ireland et al 2022), suggesting that they affect a multitude of targets in addition to their shared effects on AChE, as seen in other systems (Dam et al 2000;Slotkin 2006;Slotkin et al 2006;Yang et al 2008;Brown and Pearson 2015;Mamczarz et al 2016;Schmitt et al 2019). Here, we complement these studies and showed that D. japonica have the necessary enzymatic activity to bioactivate and detoxify OPs in adult and developing specimen and are sensitive to specific inhibitors (benzil, tacrine) known to inhibit mammalian CES and ChEs (Taylor and Radić 1994;Hyatt et al 2005;Wang et al 2018).…”
Section: Japonica Has Unique Strengths As a Non-animal Hts Model For ...mentioning
confidence: 99%